(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the features of teaching Russian as a foreign language (RFL) in the context of educational digitalization. It analyzes modern digital tools and technologies such as online platforms, mobile applications, virtual and augmented reality, and artificial intelligence, and their impact on RFL teaching methodology. Special attention is given to the advantages and challenges of digital learning, including interactivity, personalization, accessibility of educational resources, as well as issues of motivation, digital literacy, and the adaptation of traditional methods to new formats.